ความสัมพันธ์ระหว่างสินทรัพย์ไม่มีตัวตนกับราคาหลักทรัพย์และกำไรในอนาคตของบริษัทจดทะเบียนในตลาดหลักทรัพย์แห่งประเทศไทย - วรลักษณ์ โรจนรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The purpose of this study is to investigate the relationship among the reported value of intangible assets, stock prices, and future earnings of the listed firms in the Stock Exchange of Thailand. The data were obtained from the listed companies in the Stock Exchange of Thailand from 2001 to 2006. There were 878 firm-year observations collected from 228 listed firms, excluding firms in the financial sectors and the firms under the rehabilitation process. The statistical techniques used in this study consist of 1) the descriptive statistics--frequency, percent, minimum, maximum, mean, and standard deviation of the sample data, and 2) the inferential statistics--the multiple regression analysis, at 95% confidence interval used for the hypothesis testing purpose, in order to explain the relationship among intangible assets, stock prices and future earnings. The control variables are net tangible assets and current period income. Results of these tests indicate two main findings. First, the currently recognized intangible assets presented in the financial statements is statistically related to stock prices. The evidence suggests that intangible assets are value relevant. Second, a significant positive association is found between intangible assets and future period income. Goodwill is positive related to income for the 1-year to 3-year period in the future, while identifiable intangible assets have limited value relevance in the long term, and are statistically related to income at the 1-year period in the future only. This supports the proposition that intangible assets are relevant to the estimation of future period income, and provide value-relevant information.